(3OQGSI ebGQfIs - (3caGM YHO GdbGOQ(B, (3GdUhQjs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2010)
(3eGgjI GdTQcI , eaghe QCS GdeGd aj GdTQcGJ h CfhGYg h TQhWg , GdQHM h GdNSGQI h YdGbJgeG HQCS eGd GdTQcI , CMcGe GdGNJdGa aj QCS GdeGd , GdBKGQ GdeJQJHI Ydi JZjjQ QCS GdeGd aj GdTQcGJ (B.s
(3eQGLY U(B.219s
Keywords: (3GdCehGds; (3GdGbJUGO GdGSdGejs; (3GdTQcGJs; (3QCS GdeGds